Nilai PH dan Kandungan Kadar Air Bakso Ayam Broiler Dengan Menggunakan Tepung Ubi Jalar Ungu: Physicochemical quality of broiler chicken meatballs using purple sweet potato flour - Rokhayati, Umbang Arif; Sayuti M, Muhammad; Gubali, Syukri I.; Nugroho, Tri Ananda Erwin; Syahruddin, Syahruddin (UPPM Politeknik Pembangunan Pertanian Yogyakarta Magelang (Polbangtan Yoma), 2025)
Broiler chicken meat is one of the meats that plays a significant role in meeting the nutritional needs of the community. Meatballs are processed meat that has long been known and is very popular with the Indonesian people. This study aims to observe the physicochemical properties of broiler chicken meatballs using purple sweet potato flour. This study was conducted from June to October 2024 at the Animal Husbandry Laboratory, Faculty of Agriculture, Gorontalo State University. The materials and tools used include a stove, pan, knife, spoon, basin, plastic plate, cutting board, meat grinder, camera, broiler chicken, purple sweet potato flour and salt. This study was conducted using a Completely Randomized Design (CRD) with 4 treatments and 5 replications. The treatments used were P1: Meatballs with 5% purple sweet potato flour, P2: Meatballs with 10% purple sweet potato flour, P3: Meatballs with 15% purple sweet potato flour, and P4: Meatballs with 20% purple sweet potato flour. The data were processed using analysis of variance based on a Completely Randomized Design (CRD) with 4 treatments and 5 replications. Purple sweet potato flour in broiler chicken meatballs had no significant effect (P>0.05) on pH value and a significant effect (P<0.01) on water content.